A Correlation Between Duration of Gadget Use on Gross Motor and Language Development in Children Aged 3-5 Years at Posyandu Wonomulyo Polewali Mandar: Hubungan Antara Durasi Penggunaan Gadget Terhadap Kemampuan Motorik Kasar dan Bahasa pada Anak Umur 3-5 Tahun di Posyandu Wonomulyo Polewali Mandar - Citra Aulia Alwi; nurhikmawaty hasbiah (Indonesian Journal of Physiotherapy, 2025)
Background : Children at an early age are children who are in the golden age period, this period is very important for children considering that brain development reaches 80% with the growth of around 100-200 billion brain cells. So that in this golden age the potential that exists in children must be developed well. Introducing and using gadgets to children from an early age will definitely have an impact on the child's growth and development. This research has never been conducted in Wonomulyo, making researchers want to carry out further studies, especially in children aged 3 years -5 years. Objective. The general aim of this research is to determine the relationship between the duration of gadget use on gross motor skills and language development in children aged 3-5 years at Posyandu Wonomulyo. Methods : This research is a correlative descriptive study which aims to determine the relationship between the duration of gadget use on gross motor skills and language development in children aged 3-5 years at Posyandu, Wonomulyo District, Polewali Mandar Regency. The sample consisted of 51 children who met the inclusion and exclusion criteria. The duration of gadget use was measured using parent interviews, while gross motor skills and language development were measured using the Denver II test Results : Hypothesis testing was carried out using the Spearman Rank, a sig value of 0.004 (sig 0.05) was obtained, so it was concluded that there was a relationship between the duration of gadget use and gross motor skills, and a sig value of 0.001 (sig 0.05) was obtained. So a Conclusion : is obtained. that there is a relationship between the duration of gadget use and language development. There is a significant relationship between the duration of gadget use on gross motor skills and language development in children aged 3-5 years at Posyandu Wonomulyo